2015
DOI: 10.1073/pnas.1502828112
|View full text |Cite
|
Sign up to set email alerts
|

X-ray microtomography using correlation of near-field speckles for material characterization

Abstract: Nondestructive microscale investigation of objects is an invaluable tool in life and materials sciences. Currently, such investigation is mainly performed with X-ray laboratory systems, which are based on absorption-contrast imaging and cannot access the information carried by the phase of the X-ray waves. The phase signal is, nevertheless, of great value in X-ray imaging as it is complementary to the absorption information and in general more sensitive to visualize features with small density differences. Syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…At around the same time, a quantitative analysis of speckle tomography data was presented from XST measurements at a liquid metal-jet laboratory source [88]. Here, it was shown that the complementary quantitative absorption and refraction information from transmission and phase tomograms, respectively, can be combined for identifying and characterising different materials with similar refraction and absorption properties in a sample; see Figure 10V in Section 7.2.…”
Section: Speckle-based X-ray Phase-contrast and Dark-field Tomographymentioning
confidence: 97%
See 3 more Smart Citations
“…At around the same time, a quantitative analysis of speckle tomography data was presented from XST measurements at a liquid metal-jet laboratory source [88]. Here, it was shown that the complementary quantitative absorption and refraction information from transmission and phase tomograms, respectively, can be combined for identifying and characterising different materials with similar refraction and absorption properties in a sample; see Figure 10V in Section 7.2.…”
Section: Speckle-based X-ray Phase-contrast and Dark-field Tomographymentioning
confidence: 97%
“…It was demonstrated that XST tomography implemented at laboratory sources can be employed for the identification of different materials in a sample. Several types of plastic were successfully distinguished using the combined information from phase and absorption tomograms [88], as shown in Figure 10V. In another publication, the chip of a computer memory card was imaged using 1D XSS at a laboratory source, and the complementary phase and dark-field signals enabled identifying different components of the chip [136]; see Figure 10VI.…”
Section: Imaging For Biomedical and Materials Science Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, without any a priori assumption on the samples, only a few images per projection are required for multimodal tomography when employing the appropriate scheme. In contrast to previous work [19,20], the XSVT approach provides 3D rendering of the dark-field signal, in addition to the absorption and phase signals, whilst the spatial resolution of the imagery is limited only by the detector used.…”
Section: Introductionmentioning
confidence: 99%